Winners and losers - Hoffius, Stephen (New York : Aladdin Paperbacks, 1993)
When a heart condition threatens to curtail his friend Daryl's track career, Curt finds himself taking Daryl's place as lead contender for the conference championship as the new obsession of Daryl's driven father.
Keywords: Track and field -- Fiction; Fathers and sons -- Fictions; Friendship -- Fiction; Fathers and sons -- Fiction